A Research Synthesis of Therapeutic Interventions for Whiplash-Associated Disorder (WAD): Part 5 – Surgical and Injection-Based Interventions for Chronic WAD - Robert W Teasell; J Andrew McClure; David Walton; Jason Pretty; Katherine Salter; Matthew Meyer; Keith Sequeira; Barry Death (Pain Research and Management)
Whiplash-associated disorder (WAD) represents a significant public health problem, resulting in substantial social and economic costs throughout the industrialized world. While many treatments have been advocated for patients with WAD, scientific support regarding their effectiveness is often lacking. A systematic review was conducted to evaluate the strength of evidence associated with various WAD therapies. Multiple databases (including Web of Science, EMBASE and PubMed) were searched to identify all studies published from January 1980 through March 2009 that evaluated the effectiveness of any well-defined treatment for acute (less than two weeks), subacute (two to 12 weeks) or chronic (more than 12 weeks) WAD. The present article, the fifth in a five-part series, evaluates the evidence for surgical and injection-based interventions initiated during the chronic phase of WAD. Twenty-five studies were identified that met the inclusion criteria, six of which were randomized controlled trials with ‘good’ overall methodological quality (median Physiotherapy Evidence Database score of 7.5). For the treatment of chronic WAD, there was moderate evidence supporting radiofrequency neurotomy as an effective treatment for whiplash-related pain, although relief is not permanent. Sterile water injections have been demonstrated to be superior to saline injections; however, it is not clear whether this treatment is actually beneficial. There was evidence supporting a wide range of other interventions (eg, carpal tunnel decompression) with each of these evaluated by a single nonrandomized controlled trial. There is contradictory evidence regarding the effectiveness of botulinum toxin injections, and cervical discectomy and fusion. The evidence is not yet strong enough to establish the effectiveness of any of these treatments; of all the invasive interventions for chronic WAD, radiofrequency neurotomy appears to be supported by the strongest evidence. Further research is required to determine the efficacy and the role of invasive interventions in the treatment of chronic WAD.